2021
DOI: 10.21037/atm-20-1132
|View full text |Cite
|
Sign up to set email alerts
|

Current innovation in virtual and augmented reality in spine surgery

Abstract: In spinal surgery, outcomes are directly related both to patient and procedure selection, as well as the accuracy and precision of instrumentation placed. Poorly placed instrumentation can lead to spinal cord, nerve root or vascular injury. Traditionally, spine surgery was performed by open methods and placement of instrumentation under direct visualization. However, minimally invasive surgery (MIS) has seen substantial advances in spine, with an ever-increasing range of indications and procedures. For these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
0
37
0
1
Order By: Relevance
“…21 Other studies have suggested that AR may provide favorable accuracy compared with fluoroscopy-guided screw placement. [22][23][24][25] Many of these studies utilized the Gertzbein-Robbins scale to assess accuracy of pedicle screws, which allows for direct comparison between our results and this literature. However, using the classification system created by Watanabe et al 13 is less common.…”
Section: Discussionmentioning
confidence: 99%
“…21 Other studies have suggested that AR may provide favorable accuracy compared with fluoroscopy-guided screw placement. [22][23][24][25] Many of these studies utilized the Gertzbein-Robbins scale to assess accuracy of pedicle screws, which allows for direct comparison between our results and this literature. However, using the classification system created by Watanabe et al 13 is less common.…”
Section: Discussionmentioning
confidence: 99%
“…The novel development of mixed reality, or the combination of virtual and physical components, opens new perspectives in surgical planning for cranial and spine surgery. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…Studies were published between 2013 [21] and 2021 [28]. VR was used for training procedures and preoperative planning [2,3,5,21,22,27,32,33,36]. AR was utilized for preoperative planning and intraoperative purposes [2,3,11,[23][24][25][26][28][29][30][31]34,35,[37][38][39].…”
Section: Study Selection and Patient Characteristicsmentioning
confidence: 99%
“…VR was used for training procedures and preoperative planning [2,3,5,21,22,27,32,33,36]. AR was utilized for preoperative planning and intraoperative purposes [2,3,11,[23][24][25][26][28][29][30][31]34,35,[37][38][39]. AI was found reported only in two studies and was adopted to improve the preoperative diagnosis accuracy [27,33].…”
Section: Study Selection and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation